2022
DOI: 10.1186/s12903-022-02099-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal and periapical tissue response after direct pulp capping with endosequence root repair material and low-level laser application

Abstract: Background The study aims to investigate the pulp and periapical reaction and healing after capping with EndoSequence Root Repair Material (ERRM) combined with low-level laser application. Methods In 6 rabbits, pulps were exposed via class V, half of the samples received a low-level diode laser at 980 nm. Thereafter, cavities were capped with regular-set ERRM. The specimens were processed for histomorphological examination after 2 weeks and two mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Our study confirmed that if used properly, the CO 2 laser can effectively facilitate DPC, thereby increasing the treatment's success rate [42][43][44]. Irradiation with the CO 2 laser offers sufficient disinfection to the exposed pulp and the dentinal tubules in its vicinity [45][46][47][48].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our study confirmed that if used properly, the CO 2 laser can effectively facilitate DPC, thereby increasing the treatment's success rate [42][43][44]. Irradiation with the CO 2 laser offers sufficient disinfection to the exposed pulp and the dentinal tubules in its vicinity [45][46][47][48].…”
Section: Discussionsupporting
confidence: 76%
“…Overall, the study suggests that LLLT in combination with effective dental capping materials holds promise in DPC [69]. In addition, Alsofi et al concluded in a study that LLLT in combination with EndoSequence root repair material shortens the inflammatory phase and enhances the healing [44], and Alharbi et al [70] showed that LLLT combined with bioactive ERRM is effective in inducing reparative dentin formation [70]. Moreover, it is interesting to note that in our study, the success rate achieved with the 980 nm diode laser combined with Ca (OH) 2 was lower compared to Yazdanfar et al's study [28], where they reported a 100% success rate using the 810 nm diode laser.…”
Section: Discussionmentioning
confidence: 83%
“…The photo energy that penetrates into the pulp tissue coagulates the exposed pulp, thereby creating the biological basis for forming reparative dentin [ 12 ]. However, the findings of these in vitro and animal studies have shown that proper technique and materials (calcium hydroxide –Ca(OH) 2 and MTA [ 46 ]) in DPC are prioritized over optimization of PBMT [ 47 ], and so far, laboratory results have not been generalized to clinical studies [ 44 , 48 , 49 ]. Therefore, it is still unclear how to identify the contribution of a laser’s application to the clinical-outcome improvement in the irradiated group, and further studies are needed to obtain more accurate results.…”
Section: The Application Of Pbmt In Endodonticsmentioning
confidence: 99%
“…The laser-aided group showed mild inflammation, organized odontoblasts, thicker predentin in the pulp tissue, and more fibrosis in the periapical area. The histologic sections were evidence that lasers could enhance healing after direct pulp capping [ 66 ]. However, there has been some debate on the tissue response to lasers.…”
Section: Lasers In Vital Pulp Therapymentioning
confidence: 99%